A STUDY OF POLITICS OF NATIONAL IDENTITY IN SOUTH ASIA: FROM PAKISTAN AND AFGHANISTAN - Haamid Ali Shah; Humara Hashimy (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2026)
The concept of national identity in Pakistan and Afghanistan is of contested and evolving in nature. Both the countries of South Asia are highly fragmented and conflict-prone states. In this context, it is important to analyse the politics of national identity in these countries through comparative and theoretical lenses. This paper draws on constructivist, post-colonial, ethno-symbolist and instrumentalist frameworks to demonstrate that the national identity in both countries is not only historical inheritance but a continuously negotiated political project which is shaped by state narratives, ethnic pluralism, religious ideologies and external interventions. In Pakistan, the post-1947 state constructed Islam as a homogenizing national ideology intended to subsume linguistic and ethnic diversity. However, the persistent marginalization of non-Punjabi groups, tensions over linguistic imposition and the deepening of sectarian divides particularly after Zia-ul-Haq’s Islamization policies have fractured the state’s centralizing narratives which has culminated in separatist movements, internal insurgencies and crises of legitimacy. Afghanistan on the other hand, reveals a different but equally complex dynamics where Pashtun-centric state formation, multi-ethnic competition and recurring foreign interventions have impeded the consolidation of a cohesive Afghan identity. The attempt of Taliban to impose a unitary religious identity have further deepened ethnic cleavages and undermined inclusive nation-building. The comparative analysis highlights that in both the states, the identity formation is inseparable from colonial legacies, geopolitical pressures, elite manipulation and the structural weaknesses of post-colonial statecraft. The study argues that the exclusive and centralizing identity narratives have repeatedly produced cycles of violence, fragmentation and political instability. It concludes by asserting the necessity of pluralistic, inclusive and decentralized approaches to identity construction for any sustainable national cohesion in Pakistan and Afghanistan.